Anti-metastatic action of an N4-aryl substituted thiosemicarbazone on advanced triple negative breast cancer - Sólimo, Aldana María (2020)
Purpose: Advanced triple negative breast cancer (ATNBC) is defined by a lack of expression of hormones receptors as well as HER2/neu and its high probability of visceral metastasis. This pathology is associated with a poor prognosis. Previously, we found that T2, an N4 -arylsubstituted thiosemicarbazone (N4 -TSC), had cytotoxic effect on human breast cancer cells lines. Hence, in this study, we investigated the anti-metastasic action of T2 on ATNBC. Methods: In order to deepen T2 action mode on ATNBC, we first confirmed T2 cytotoxicity on a panel of TNBC cells and then continued studying T2 effects in vitro an in vivo on the syngeneic 4T1 mouse model. Results: We found that T2 had a cytotoxic effect comparable to chemotherapeutics used in present treatment schemes for ATNBC. T2 treatment not only induced apoptosis, but it also down-modulated 4T1 invasive and metastatic-associated capacities, such as clonogenicity, migration and metallo-proteases activity. Moreover, this agent reduced the number of 4T1 cancer stem cells. Finally, T2 treatment induced a more differentiated cell phenotype and the overexpression of the metastasis suppressor gene NDRG-1. In vivo assays showed that T2 reduced tumor burden, down modulated local tumor invasion and significantly reduced the number of lung metastases in the 4T1 advanced TNBC murine model, while the compound did not exhibit intolerable toxicity. Conclusion: This study provided evidence that T2 not only exerted an anti-tumor activity but it also showed antiinvasive and anti-metastatic actions on ATNBC in vivo and in vitro, suggesting that T2 could be considered as a promising therapy that deserves further analysis.